Manufacturing flexibility through outsourcing: effects of contingencies. Issue 9 (26th August 2014) - Scherrer-Rathje, Maike; Deflorin, Patricia; Anand, Gopesh
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the influence of organizational context on the relationships between outsourcing and manufacturing flexibility. In doing so, the authors study four types of manufacturing flexibility: product, mix, volume, and labor competence flexibility. Design/methodology/approach – Based on transaction cost economics theory and resource-based view of competitive advantage, the authors focus on economies of scale and scope, asset specificity, organizational learning, and dynamic capabilities as contingencies affecting outsourcing-flexibility relationships. Combining theoretically developed propositions with insights from case studies of 11 manufacturing companies that outsourced some portion of their manufacturing, the authors derive grounded hypotheses. Findings – Empirical results show that in some cases the effects of outsourcing on different types of manufacturing flexibility vary based upon some contingency factors. Research limitations/implications – Due to the qualitative nature and the geographical focus of the empirical examination, applicability of the findings to other contexts may be limited. Practical implications – The authors point out specific contingencies that managers should consider when targeting manufacturing flexibility through outsourcing. Originality/value – This paper presents the interrelationships among outsourcing of manufacturing activities, four types of manufacturing flexibilities, and theoretically derived contingencies. Based on evidence from the analyzed cases, the authors find indications that some contingencies moderate outsourcing-flexibility relationships. In addition, this paper introduces a new type of manufacturing flexibility: labor competence flexibility, which is defined as the ability of a company's workforce to deal with technology driven additions to and subtractions from products over time.